2011
DOI: 10.1007/s11605-011-1457-2
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid Diverticulitis in Young Patients—A More Aggressive Disease than in Older Patients?

Abstract: Acute SD in younger patients is not more aggressive and has no higher risk of perforation or need for emergency surgery compared to older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
2
35
0
1
Order By: Relevance
“…However, whether they are at increased risk of complications or recurrent attacks remains debatable [7,27]. Large patient studies performed in recent years have demonstrated that the risk of recurrence or complications is not higher in younger than in older patients [13,28,29]. Our data suggest that recurrence of diverticulitis seems not be influenced by age.…”
Section: Discussionmentioning
confidence: 59%
“…However, whether they are at increased risk of complications or recurrent attacks remains debatable [7,27]. Large patient studies performed in recent years have demonstrated that the risk of recurrence or complications is not higher in younger than in older patients [13,28,29]. Our data suggest that recurrence of diverticulitis seems not be influenced by age.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, any increased risk is a chronologic rather than pathologic phenomenon [38]. Acute diverticulitis in the young could be managed as in the older patients [16], the indication for surgery being not dependent on age but on the actual clinical findings [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies would suggest that younger age is a risk factor for recurrent disease; however, these patients are just as likely to respond to conservative management. [52][53][54][55] SMOKING There have been a number of studies investigating the relationship between smoking and diverticular disease. The Swedish mammography cohort study investigated 36,000 women of whom 560 had an admission for diverticulitis during the study period.…”
Section: Age and Gendermentioning
confidence: 99%